Functional indicators of vitamin D adequacy for very low birth weight infants. (May 2018) - Taylor, Sarah; Wahlquist, Amy; Wagner, Carol; Ramakrishnan, Viswanathan; Ebeling, Myla; Hollis, Bruce
Abstract Objective To identify the vitamin D status to optimize calcium and bone health in preterm infants. Study design Very low birth weight infants had measurement of 25-hydroxyvitamin D status and markers of calcium and bone health from birth to term age. Piecewise linear regression modeling was performed to identify a 25-hydroxyvitamin D threshold associated with stable parathyroid hormone concentration and bone mineralization. Results In a cohort of 89 infants at term age, femur BMC and density increased linearly with 25-hydroxyvitamin D status until reaching a threshold of 48 ng/mL and 46 ng/mL, respectively. Parathyroid hormone status decreased as vitamin D status increased until reaching a plateau at 25-hydroxyvitamin D of 42 ng/mL. Conclusion Preterm infant vitamin D status was significantly associated with PTH status and femur mineralization with suggestion that achieving a specific 25-hydroxyvitamin concentration is associated with optimal calcium homeostasis and femur bone mineralization.